2010
DOI: 10.1038/sc.2010.99
|View full text |Cite
|
Sign up to set email alerts
|

Extent of spontaneous motor recovery after traumatic cervical sensorimotor complete spinal cord injury

Abstract: Study design: Retrospective, longitudinal analysis of motor recovery data from individuals with cervical (C4-C7) sensorimotor complete spinal cord injury (SCI) according to the International Standards for Neurological Classification of Spinal Cord Injury (ISNCSCI).Objectives: To analyze the extent and patterns of spontaneous motor recovery over the first year after traumatic cervical sensorimotor complete SCI. Methods: Datasets from the European multicenter study about SCI (EMSCI) and the Sygen randomized clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
125
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 166 publications
(131 citation statements)
references
References 26 publications
1
125
1
1
Order By: Relevance
“…Recovery of function in two or more spinal segments is less common. 46 The more extensive motoneuron death reported here one level caudal to the lesion epicenter may explain why more recovery is not always apparent clinically, even though this is the level where functional return is expected to occur. Further, the extent of muscle denervation will depend on the longitudinal extent of the lesion, which is unexplored clinically.…”
Section: Grumbles and Thomasmentioning
confidence: 98%
“…Recovery of function in two or more spinal segments is less common. 46 The more extensive motoneuron death reported here one level caudal to the lesion epicenter may explain why more recovery is not always apparent clinically, even though this is the level where functional return is expected to occur. Further, the extent of muscle denervation will depend on the longitudinal extent of the lesion, which is unexplored clinically.…”
Section: Grumbles and Thomasmentioning
confidence: 98%
“…The limitations of using the AIS as an instrument to measure outcomes have been discussed in previous studies and more recent studies have tended to use the AIS grade conversion and motor scores simultaneously, or they have proposed that detecting sensory and motor changes may require more sensitivity than measuring AIS grade conversion, especially when attempting to calculate therapeutic efficacy. 8,9 Many studies in the literature have focused on AIS conversion in SCI patients, but, to the best of our knowledge, only the study by Spiess et al 3 reported a conflict between AIS grade conversion and neurological changes. They reported only 1 out of a total of 90 patients, based on the data from the European Multicenter Study on Human Spinal Cord Injury, was converted from AIS B to AIS D owing to a change in motor level arising from sensorial deterioration without a gain in muscle score.…”
Section: Discussionmentioning
confidence: 96%
“…An improvement in many muscles from a motor score of 0 to a score of 1-2 connotes different functional implications than do gains in a few muscles to X3. 12 In addition, a number of the CUE-Q items (reaching out or up) involve shoulder muscles that are not included Figure 1 Scatterplots of total CUE-Q scores and upper extremity motor scores (upper graphs) and self-care FIM scores (lower graphs) at admission and discharge from inpatient rehabilitation. Two subjects had unusual patterns of responses.…”
Section: Discussionmentioning
confidence: 99%